A bibliometric study of the European Super League of football – A new plan or an old threat?. (17th November 2022) - Macedo, Anthony; Ferreira Dias, Marta; Mourão, Paulo Reis
ABSTRACT: The year 2021 was critical for European football, as the COVID-19 pandemic led to financial problems that brought back the idea of top clubs creating a European Super League (ESL). This idea has been popular in the past, but its discussion in scientific literature has generally been brief and infrequent. Seen by some authors as the salvation of the industry and by others as a threat, this is a topic that promises not to disappear any time soon. Therefore, this bibliometric review intends to identify the trends and gaps in the literature, the directions followed in each work, and the networks between authors, as well as to highlight the main contributors. Such a review will help set out a future research agenda on this topic.